Disregarding the Reproductive Rights of Women in Child Marriage in Indonesia - Huzaimah, Arne; Abdillah, Muhammad; Laila, Nur Quma; Tamudin, M.; Puji Astuti, Tri Marhaeni (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
The phenomenon of child marriage frequently disregards children's reproductive rights. This study aims to explain the negligence of reproductive rights in child marriages by examining practices, factors, and the impacts of such neglect on girls' human rights. This paper employs a qualitative descriptive approach, and the data was gathered through the use of keywords to search the term "neglect of women's reproductive rights in child marriage”. The data was analyzed by reducing, describing, and interpreting the data in depth in order to reach a conclusion. This paper demonstrates that the practice of child marriage not only places females in a disadvantageous position, but also has an impact on reproductive rights, which has negative repercussions for survival, such as miscarriage, baby blues syndrome, and death. It is also anticipated that this paper can serve as a resource for conducting research on child marriage and the neglect of girls' reproductive rights from a broader and more multidisciplinary perspective, so that it can be used as a basis for formulating firm policies on reproductive rights